The spleen in Carrion's disease - Hercelles, Oswaldo (1918)
Among the organs that play important role in Carrion's disease, spleen occupies undoubtedly the first place. Thus, since the beginning of the disease, spleen combat anemia, which is the characteristic of this period, when the bone is still insufficient to repair the increasingly heavy losses desglobulizador process; is this body which defends, in large part, to the warty so frequent bacterial complications in this disease; and, finally, spleen, even though it seems paradoxical, the cause of death of the patient; either by colapsus of the viscera to the hematopoietic paper or septicemia which determines its embolizing their arteries claudication.